Pengaruh Penambahan Trikalsium Fosfat Dan Jenis Starch Pada Pembuatan Biokeramik Berpori Menggunakan Metode Starch Consolidation - Yuliestri, Erika Rezi; Yenti, Silvia Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tricalcium phosphate (TCP) is one of the compound of hard tissues the human body that can be applied in the medical. One of technique for making porous tricalcium phosphate is starch consolidation method. The objective of this research is to study effect of adding tricalcium phosphate and starch type of porous tricalcium phosphate. This research was conducted in mixing tricalcium phosphate powder as much as 6 ; 7 ; and 8 gram with 3 gram of sago starch or corn starch, as well as 10 ml aquadest. The slurry was stirred for 1 hour and dried in oven at oven 80ËC for 24 hours and 120ËC for 8 hours. The dryed green bodies were burnt at a temperature of 600ËC and sintered at a temperature of 1300ËC. Porous tricalcium phospate prepared using corn starch has a higher compressive strength than the porous tricalcium phospate using sago starch. The addition of tricalcium phosphate result in smaller porosity and density as well as greater shrinkage and also higher compressive strength. Sintered tricalcium phosphate bodies shows that the shrinkage in the range of 47,66â62,31%, porosity 23,81-32,07%, density 0,67-0,76 gr/cm3compressive strength 2,87-3,71 MPa.Keywords: Compressive strength; Porosity; Starch; Tricalcium phosphate